2008
DOI: 10.1017/s1074070800028091
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Economic Impact of Farmers' Markets Using an Opportunity Cost Framework

Abstract: Farmers' markets presumably benefit local economies through enhanced retention of local dollars. Unlike other studies, the net impact of farmers' markets on the West Virginia economy is examined. Producer survey results are used in estimating annual direct sales ($1.725 million). Using an IMPLAN-based input-output model, gross impacts are 119 jobs (69 full-time equivalent jobs) and $2.389 million in output including $1.48 million in gross state product (GSP). When the effect of direct revenue losses are includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
99
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(103 citation statements)
references
References 4 publications
0
99
0
Order By: Relevance
“…A more thorough accounting of the opportunity cost of resources and spending tied to LFSs is needed. The limited existing research that accounts for the opportunity cost for farmers' markets indicates that the reduction in economic impact is substantial (Hughes et al, 2008;Hughes & Isengildina-Massa, 2013). Further, the opportunity cost of inputs used in LFSs also should be considered.…”
Section: Model Use and Results Interpretationmentioning
confidence: 99%
See 2 more Smart Citations
“…A more thorough accounting of the opportunity cost of resources and spending tied to LFSs is needed. The limited existing research that accounts for the opportunity cost for farmers' markets indicates that the reduction in economic impact is substantial (Hughes et al, 2008;Hughes & Isengildina-Massa, 2013). Further, the opportunity cost of inputs used in LFSs also should be considered.…”
Section: Model Use and Results Interpretationmentioning
confidence: 99%
“…Regional or local input-output models have been used to estimate the economic impact of LFS through specific marketing channels (e.g., farmers' markets (Hughes, Brown, Miller & McConnell, 2008); direct to institutional foodservice establishments (Thilmany, Gunter, & Sullins, 2011) or production potentials (Swenson, 2011)). In general, such models are in need of improvement to better reflect the constraints and impacts of LFSs.…”
Section: The Economic Impact Of Lfss Can Be Quantified and Is Substanmentioning
confidence: 99%
See 1 more Smart Citation
“…Local sales result in greater regional economic impacts when compared to food sales via traditional retail markets (Hughes, et al 2008;Hughes and Isengildina-Massa 2015;Jablonski, Schmit, and Kay 2016;Rossi, Johnson, and Hendrickson 2017). In addition to generating income for producers, they can also provide an economic boost to other local businesses that provide ancillary services to the sector.…”
Section: Overview Of Local Food Systemsmentioning
confidence: 99%
“…Although many FM studies focus on the economic impact of FMs (Hughes et al 2008), or on effective marketing or advertisement techniques (Baker et al 2009;Berry et al 2013), few highlight how governance might influence these techniques. Gantla and Lev (2016) examined ownership structures of FMs in Oregon and found that 2 These concepts are derived from Marjorie Kelly's Architecture of Ownership the foundation of her Generative Ownership concept (Kelly 2012).…”
Section: Finance and Marketingmentioning
confidence: 99%